Komunikasi Simbolik dalam Tradisi Perang Bangkat sebagai Media Pembentukan Keluarga Sakinah Masyarakat Suku Osing di Desa Kemiren Kecamatan Glagah Kabupaten Banyuwangi - Moch. Syahrul Rizki; Mashudi Mashudi; Saihan Saihan (Lembaga penelitian dan pengabdian kepada Masyarakat, 2026)
This study examines symbolic communication in the tradition of the rank war ceremony as a medium for the formation of a sakinah family in the Osing Tribe community in Kemiren Village, Glagah District, Banyuwangi Regency. The tradition of war is a traditional marriage ritual carried out on couples with a certain order of birth and is believed to contain philosophical, social, and religious values in building family harmony. Although a number of studies have addressed this tradition from the perspective of Islamic law and cultural semiotics, studies that integrate the perspective of symbolic communication and the concept of the sakinah family comprehensively are limited. This research uses a qualitative approach with the type of field research in Krajan Hamlet and Kedaleman Hamlet, Kemiren Village. Data was collected through observation, in-depth interviews, and documentation, then analyzed using George Herbert Mead's theory of symbolic interaction. The results of the study show that: (1) the Osing people maintain the tradition of the rank war because it contains relevant social, cultural, and religious meanings; (2) the procession of the war of the rank includes the bridal procession, the puppeteer war, the ngosek ponjen, and the joint prayer representing the values of responsibility, communication, and social solidarity; (3) Traditional symbols in the war actualize the values of the Sakinah family, namely loyalty, mutual understanding, family respect, and strengthening spirituality. These findings show that local traditions can be an effective symbolic communication medium in internalizing harmonious family values in the midst of Indonesian Muslim society.